Arenibacter aquaticus sp. nov., a marine bacterium isolated from surface sea water in the South China Sea. Issue 2 (15th November 2019) - Guo, Jiaying; Sun, Jia; Xu, Yongle; Fang, Lüping; Jiao, Nianzhi; Zhang, Rui
Abstract : A Gram-stain-negative and facultatively anaerobic bacterial strain, designated GUO T, was isolated from surface water collected from the South China Sea. Cells were non-flagellate, yellow, non-spore-forming and rod-shaped. The 16S rRNA gene sequence comparisons with species in the genus Arenibacter showed that strain GUO T shares the highest similarity of 97.5 % with Arenibacter echinorum and Arenibacter palladensis . Average nucleotide identity and digital DNA–DNA hybridization values between strain GUO T and its related type strains were 77.1–78.4% and 20.8–26.2 % respectively. Growth of strain GUO T occurred at 15–50°C (optimum, 20–25°C), pH 5–7.5 (pH 6) and in media containing 0–7 % NaCl (optimum, 0–1 %). Cells contained methanol-soluble yellow-coloured pigments but flexirubin-type pigments were absent. The major fatty acids (>5 %) were iso-C17 : 0 3-OH, iso-C15 : 0, anteiso-C15 : 0, C16 : 0, summed feature 3, iso-C15 : 1 G and iso-C15 : 0 3-OH. The dominant polar lipids comprised phosphatidylethanolamine and some unidentified polar lipids. The main respiratory quinone was menaquinone-6. The DNA G+C content of strain GUO T was 40.1 %. Based on the presented data, we consider strain GUO T to represent a novel species of the genus Arenibacter, for which the name Arenibacter aquaticus sp. nov. is proposed. The type strain is GUO T (=KCTC 62629 T =MCCC 1K03559 T )